Exploration of the initiation and process of business model innovation of successful Chinese ICT enterprises. Issue 4 (4th November 2019) - Liu, Peng; Bell, Robin
Abstract : Purpose: This paper aims to investigate four successful Chinese ICT enterprises to determine what initiated their business-model innovations and the process they went through by exploring how they adapted and innovatively renewed four key elements of their business models. Design/methodology/approach: This investigative and exploratory research adopted a multiple-case-study design exploring four purposively selected successful Chinese ICT enterprises which had all engaged in significant business model innovation since their inception. Data for the case studies were collected through in-depth interviews with the founders and analyses of the companies' history to gain a detailed account of the evolution of the firms' business models since their formation. Findings: The research identified three key initiating factors to business model innovation in the firms studied, namely, constant and rapid product iteration, along with an emergent strategy, leading to business model innovations to take full advantage of the firms' competitive advantages; a reaction to threats and environmental changes; and an opportunistic behaviour to extend the business model to new markets. The research found that networks were a key factor in the process, including the customer base, financial investors and network collaborators. Research limitations/implications: This research is limited to four successful Chinese ICT firms; this in-depth approach means the information may have only limited transferability but provides depth on a burgeoning Chinese sector. Originality/value: This research addresses the call for more research and a greater understanding of what initiates business model innovation and the process firms go through to develop the key elements of their business models by looking at a purposively selected sample of successful Chinese enterprises in a fast-moving and technologically driven market.